Cutting system influence on production and nutritional value of wheat cv. BRS Umbu for forage (Revista de Ciências Agroveterinárias, 2020)
The optimization of pasture management is essential for obtaining higher productive levels, and dual-purpose cereals have stood out and can be used for different purposes within the property through different management strategies. The objective was to evaluate the biomass production and the nutritional value of wheat forage (Triticum aestivum L. cv. BRS Umbu) under the influence of successive cutting regimes simulating grazing situations. The experimental design used was in randomized blocks, composed of three treatments (without cut - control; one cut; and two cuts performed) with five replications. For accumulated dry biomass production, average values of 10,926 kg ha-1 were observed for the treatment without cutting, 7,989 kg ha-1 for the treatment with one cut and 3,514 kg ha-1 for the treatment with two cuts. There was a difference between the leaf: stem ratio, this factor being reduced according to the increase in the number of cuts (4.14; 2.36 and 2.24 for without cut, with one and two cuts, respectively). In the bromatological composition, no significant differences were found for the crude protein, acid detergent fiber and neutral detergent fiber contents. The increase in the number of cuts does not reduce the accumulated green biomass yield, but a significant decrease in the percentage of leaves can lead to lower dry biomass production. As bromatology was not altered by the cutting regime, better productive results can be seen with one cut and/or grazing system.
Keywords: dual purpose; dry biomass production; Heat Shock Protein; Triticum aestivum L.